Liturgical movements in culture and society - Rouwhorst, Gerard (Jaarboek voor liturgieonderzoek, 2006)
These comments concern the historical antecedents of the situation sketched by Post, and the possible implications for the study of liturgical history of his plea for a matrix for innovative liturgical studies.